A Working model towards promoting corporate governance best practices in Zimbabwe’s mining sector: the case of Shamva gold mine. - Makanda, Martin Chamunorwa (BUSE, 2023)
The research assessed the promotion of corporate governance best practices in the mining sector of Zimbabwe. The mining sector is a crucial part of the Zimbabwean economy that contributes huge foreign currency from exports of minerals. The study sought to ensure the promotion of good corporate governance best practices according to international standards in the mining sector of Zimbabwe. Literature review reveals that corporate governance is crucial in a developing economy where its application is limited to few structures at Shamva Gold Mine which resemble box-ticking. The box-ticking enables mining companies to implement piece-meal approaches to good governance thereby exposing the mining sector rampant leakages of minerals. It was also noted that the mining sector needs to be capacitated with strong legislation, policies and strengthening of current corporate governance code. This helps to promote and improve good corporate governance across all sectors of the economy.
Keywords: Corporate Governance; Mining Sector; Shamva Gold Mine